A comparative analysis of hydrogen production from the thermochemical conversion of algal biomass. (23rd April 2019) - Kumar, Mayank; Oyedun, Adetoyese Olajire; Kumar, Amit
Abstract: Gasification has the potential to convert biomass into gaseous mixtures that can be used for hydrogen production. Thermal gasification and supercritical water gasification are commonly used thermochemical methods for conversion of biomass to hydrogen. Supercritical water gasification handles wet biomass, thus eliminating the capital cost-intensive drying step. Thermal gasification is considered as an alternative means of producing hydrogen from microalgae where biomass has to be dried before gasification. The authors developed techno-economic models for assessment of the production of hydrogen through supercritical gasification and thermal gasification processes. Techno-economic assessment was based on developed process models. Equipment was sized and costs were estimated using the developed process models, and the product value was determined assuming 20 years of plant life. The economic assessment of supercritical water and thermal gasification show that 2000 dry tonnes/day plant requires total capital investments of 277.8 M and 215.3 M for hydrogen product values of 4.59 ± 0.10/kg and 5.66 ± 0.10/kg, respectively. The relatively higher yield obtained in supercritical water gasification compared to thermal gasification results in lower product value of hydrogen for supercritical water gasification, thereby making it more desirable. This cost of hydrogen is about 4 times the cost of hydrogen from natural gas. The sensitivity analysis indicates that biomass cost and yield are the most sensitive parameters in the economics of the supercritical or thermal gasification process; this signifies the importance of algal biomass availability. The techno-economic assessment helps to identify options for the production of hydrogen fuel through these novel technologies. Highlights: The production of hydrogen from thermochemical algal conversion is assessed. Data-intensive techno economic model is developed to determine the product value. The cost of hydrogen from algal thermochemical processing varies from 4.59 to 5.66 /kg. The impact of CO2 tipping fee on cost of hydrogen was assessed.